Combined Gamma Irradiation and Hydrothermal Treatments did not adversely affect the Nutritional Characteristics of African Bush Mango (Irvingia gabonensis) Seeds and the Oil Quality - Fagbemi, Stephen A.; Asunni, Alex O.; Olorunnusi, Johnson O.; Okeji, Mercy A.; Enujiugha, Victor N. (Journal of Agriculture, Food Technology and Sustainability, 2024)
The need to preserve the nutrients in a food sample while ensuring microbiological safety has led to researches on different hurdle techniques. To this end, this study aimed at evaluating the effect of gamma irradiation and hydrothermal treatment in a hurdle arrangement on the physicochemical and functional properties of bush mango (Irvingia gabonensis) seed, as well as investigation of its impact on quality attributes of the oil. The Irvingia gabonensis samples were divided into raw, cooked, cooked and irradiated at 10 kGy, and irradiated at 5 kGy and 10 kGy, respectively. Proximate composition, minerals, antinutritive factors, oil quality and amino acid profile were determined in the differently treated samples. It was observed that increase in gamma irradiation dose, as well as the hurdle treatment, reduced the protein content of the samples. Tannins, iodine value and free fatty acid were all reduced with increased irradiation dose and additional hydrothermal treatment. On the other hand, no significant difference was observed in water and oil absorption capacities and foaming stability of the seed samples. The amino acid profile indicated various increases in isoleucine, valine, threonine, glutamic acid, alanine, and tyrosine as irradiation dose increased, while lysine, glycine, leucine, phenylalanine and methionine showed decreases. It could be deduced from the findings that, apart from increased saturation of the seed oil, the hurdle arrangement of gamma irradiation and cooking did not adversely affect the nutritional status of the bush mango seed.